1990
DOI: 10.2307/2409287
|View full text |Cite
|
Sign up to set email alerts
|

Allopatric Origin of Sympatric Populations of Lake Whitefish (Coregonus clupeaformis) as Revealed by Mitochondrial-DNA Restriction Analysis

Abstract: In the paper, restriction-fragment length polymorphisms in mitochondrial DNA (mtDNA) were studied to test the hypothesis that sympatric populations of lake whitefish in the Allegash basin have recently diverged through sympatric speciation. Thirteen restriction enzymes were used to analyze mtDNA of 156 specimens representing 13 populations from eastern Canada and northern Maine where normal and dwarf phenotypes of whitefish exist in sympatry and allopatry. Two monophyletic assemblages of populations that exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
198
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(215 citation statements)
references
References 19 publications
16
198
1
Order By: Relevance
“…The origin of polymorphism in Arctic charr and other freshwater fish has been explained by several hypotheses, ranging from allopatric divergence under geographical isolation during the last Ice Age, to divergent natural selection in sympatry (Nyman et al 1981;Klemetsen 1984;Bernatchez and Dodson 1990;Lu and Bernatchez 1999;Schluter 2000;Dieckmann et al 2004). Sympatric speciation has become increasingly accepted during the past decades, and the link between ecological differentiation and reproductive isolation seems particularly important in the evolution of postglacial fishes (Schluter 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of polymorphism in Arctic charr and other freshwater fish has been explained by several hypotheses, ranging from allopatric divergence under geographical isolation during the last Ice Age, to divergent natural selection in sympatry (Nyman et al 1981;Klemetsen 1984;Bernatchez and Dodson 1990;Lu and Bernatchez 1999;Schluter 2000;Dieckmann et al 2004). Sympatric speciation has become increasingly accepted during the past decades, and the link between ecological differentiation and reproductive isolation seems particularly important in the evolution of postglacial fishes (Schluter 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, empirical evidence shows a sympatric origin for divergence of some freshwater fish, for example the African cichlids, (Schliewen et al, 1994) although an allopatric origin has been suggested for others (see e.g. Bernatchez and Dodson, 1990 on Lake Whitefish Coregonus clupeaformis). Theoretical objections to the process of sympatric divergence have now largely been resolved (see Tregenza and Butlin, 1999) and a number of models proposed that identify a significant role for resource acquisition in evolutionary divergence in sympatry (Schluter, 1996;Dieckmann and Doebeli, 1999;Kondrashov and Kondrashov, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic distances between the studied populations were less than those observed for C. lavaretus from Polish lakes (Kohlmann et al 2005). In addition, the weak mtDNA divergence between sympatric pairs of C. l. pidschian and C. l. pravdinellus species suggests that their speciation was accompanied by only minor alterations of the ancestral gene pool, as was reported for the lake whitefishes in eastern North America (Bernatchez and Dodson 1990). Probably, these sympatric morphs evolved allopatrically in separate refugia and independently colonised Lake Teletskoye.…”
Section: Discussionmentioning
confidence: 74%
“…The occurrence of many whitefish haplotypes and morphs in the lakes may result from a historical mixing of different populations and lineages and their secondary contact, as it was suggested for the whitefishes of Europe and North America (Bernatchez and Dodson 1990;Bernatchez and Wilson 1998;Kohlmann et al 2005;Østbye et al 2005). To conclude, the water bodies of the southern part of Siberia represent a secondary contact zone for the distinct phylogenetic lineages of Coregonus lavaretus pidschian.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation